Multicilin and activated E2f4 induce multiciliated cell differentiation in primary fibroblasts - Kim, Seongjae (Sci Rep, 2018)
Multiciliated cells (MCCs) are specialized epithelial cells that project hundreds of motile cilia. To form these cilia, MCCs differentiate by dramatically expanding centriole number, using assembly factors required for centriole duplication during the cell cycle and multiple, novel assembly sites, called the deuterosome. The small coiled-coil protein, Multicilin, acting in a complex with the E2F proteins can initiate multiciliated cell differentiation, but reportedly only in a limited range of epithelial progenitors. To examine the nature of this restricted activity, we analyzed Multicilin activity in primary mouse embryonic fibroblasts (MEFs), a cell type distant from the epithelial lineages where MCCs normally arise. We show that Multicilin transcriptional activity is markedly attenuated in MEFs, where it induces only limited centriole expansion in a small fraction of cells. We further show that this transcriptional block is largely bypassed by expressing Multicilin along with a form of E2f4 where a generic activation domain from HSV1 VP16 (E2f4VP16) is fused to the carboxy terminus. MEFs respond to Multicilin and E2f4VP16 by undergoing massive centriole expansion via the deuterosome pathway, recapitulating a temporal sequence of organelle biogenesis that occurs in epithelial progenitors during MCC differentiation. These results suggest that the pattern of organelle biogenesis occurring in differentiating MCCs is largely determined by the transcriptional changes induced by Multicilin.